The impact of the manifestations of consistency in directing semantics andinterpretation of poetic discourse - an applied study on the Algerian nationalanthem in the light of the textual linguistic approach (Numerus academy review, 2026)
The study aims to investigate the poem of the national anthem according to the perspective of the textual linguistic approach, which is based in its analysis of the texts on identifying the tools and mechanisms that ensure the text’s verbal continuity and semantic coherence, by standing on the manifestations of its consistency andcoherence factors; The study takes the Algerian national anthem as an applied field,limited to determining the manifestations of textual consistency in the poem, which we summarize in reference, replacement, deletion, kindness and lexical consistency. and ifso; What are the mechanisms and means used by the poet "Mofdi Zakaria" to achievethis textual interconnection? What is the role of these mechanisms in understandingthe significance of the poetic poem? In order to confront these questions and analyzethis poetic discourse in a textual and linguistic way; I employed the descriptiveapproach with activating the mechanisms of analysis.